Evaluation of the Reproducibility and Robustness of Extrusion-Based Bioprinting Processes Applying a Flow Sensor - Strauß, Svenja; Schroth, Bianca; Hubbuch, Jürgen (Frontiers in Bioengineering and Biotechnology, 2022)
Bioprinting is increasingly regarded as a suitable additive manufacturing method in biopharmaceutical process evelopment and formulation. In order to manage the leap from research to industrial application, a high level of reproducibility and a standardized bioprinting process are prerequisites. This said, the concept of process analytical technologies, standard in the biopharmaceutical industry, is still at its very early steps. To date extrusion-based printing processes are set pressure controlled and thus not adaptive to changes (environmental or system related) occurring over several runs. A constant set pressure applied over a number of runs, clearly might lead to unpredictable variations in flow rate and thus to unreliable prints. With this in mind, the simple question arises whether a printing process based on a set flow rate over several runs and thus individual prints or technical replicates might improve reproducibility and eases parameter transferability over different devices. This study thus investigates changes in printing accuracy due to processing modes (set pressure vs. set flow rate) occurring during an extrusion-based printing process consisting of 6 runs with 3 sample prints each. Additionally, the influence of different filling levels of the ink containing cartridge during a print was determined. The need for individual settings among different hydrogels was analyzed using two types of hydrogels, based on alginate and Kolliphor in different concentrations. To investigate parameter transferability among different devices two different printer were used. The above was facilitated by attaching a flow sensor to the different printing systems. It could be demonstrated that a set flow rate controlled printing process improved accuracy and that the filling level of a cartridge needs to be taken into account as a dynamic parameter during a print. The change from a system dependent parameter (pressure) to a physical parameter (flow rate) furthermore eased the transferability between different printing devices. Finally, by a simple flow rate setup the coefficient of variance for printed objects could be reduced from 0.2 to 0.02 for 10 % (w/v) alginate hydrogels.